2003
DOI: 10.1080/08037050310009545
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Isolated Systolic Hypertension: The SHELL Study Results

Abstract: In elderly patients with isolated systolic hypertension, administration of lacidipine or chlorthalidone markedly reduced systolic blood pressure with no difference in the incidence of cardiovascular events and total mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 4 publications
0
40
1
Order By: Relevance
“…As the guidelines partly used the same studies, this resulted in 21 trials for analysis, including two recent trials not yet cited in these guidelines [12,13,17]. Together with additional references to studies' design, protocol, or patients' characteristics 47 articles were analyzed [12e58].…”
Section: Resultsmentioning
confidence: 99%
“…As the guidelines partly used the same studies, this resulted in 21 trials for analysis, including two recent trials not yet cited in these guidelines [12,13,17]. Together with additional references to studies' design, protocol, or patients' characteristics 47 articles were analyzed [12e58].…”
Section: Resultsmentioning
confidence: 99%
“…10 Indeed, monotherapy based on CCBs has demonstrated to provide sustained antihypertensive efficacy and to reduce cardiovascular and renal complications compared to other antihypertensive drug classes. [37][38][39][40][41][42] In those patients with hypertension who do not achieve satisfactory BP control under monotherapy, or in those with high or very high cardiovascular risk profile, a combination strategy based on the use of 2 classes of antihypertensive drugs, including either ARBs or ACE inhibitors plus CCBs or thiazide diuretics (dual combination therapy) should be used. Randomized clinical trials [43][44][45] and large meta-analyses 46,47 confirmed that these combination strategies are characterized by an antihypertensive efficacy about 5 times greater than the doubling of the dose of each monotherapy.…”
Section: Current Recommendations For Hypertension Treatment and Controlmentioning
confidence: 99%
“…There were three papers reporting bendrofluazide 9-11 outcomes, two papers using chlorothiazide, 12,13 five papers reporting five outcomes for chlorthalidone, [14][15][16][17][18] 10 papers using hydrochlorothiazide 9,11,[19][20][21][22][23][24][25][26] and one paper reporting on indapamide 27 (table 1). two of these studies used bendrofluazide or hydrochlorothiazide.…”
Section: Resultsmentioning
confidence: 99%